Effect of Bushen Yutai Recipe on IVF Patients Subjected to Mild Ovarian Stimulation - Jiang, Xiaomei; Yan, Hua; Zhong, Xiufang; Tong, Guoqing; Zhang, Wuwen (Frontiers in Medicine, 2020)
This article investigated the effects of the traditional Chinese medicine (TCM) herbal recipe, Bushen Yutai, on in vitro fertilization (IVF) patients subjected to mild ovarian stimulation. Two hundred nineteen infertile patients were randomly divided into 2 groups: the control group and herbal treatment group. By studying, we found estrogen levels (E2) on the human chorionic gonadotropin (hCG) triggering day were significantly lower in the control group (P < 0.05), with positive blood flow being less detected by ultrasound scanning on both the day of hCG triggering and day of fresh embryo transfer for the control group (P < 0.05). Additionally, the blood flow index, retroactive and proactive inhibition, was higher in the control group, whereas the fertilization rate and number of high-quality embryos in the control group were lower than the control TCM experimental group (P < 0.01). The expression levels of the endometrial receptivity gene, vascular endothelial growth factor (VEGF), were lower in the control group vs. the TCM experimental group on the day of fresh embryo transfer (P < 0.05), whereas the rate of fresh embryo transfer in the control group was lower than the TCM experimental group (P < 0.05). In conclusion, the TCM could increase the E2 during the IVF stage, with a higher number of oocytes and higher-quality embryos. It also improved the endometrium and increased the level of VEGF gene expression. By enhancing the fresh embryo transfer rate in a minimal ovarian stimulation protocol and by improving the clinical pregnancy and ongoing pregnancy rates, the Bushen Yutai recipe could be able to increase fresh embryo transfer and higher-quality embryos.